Improvement of management of company cash - Matiukhina, A. (Літограф, 2017)
Economic uncertainty, rising debt levels, and increased scrutiny from shareholders and analysts are driving greater focus on maximizing cash flow. Some companies are rising above these challenges. By adopting working capital management best practices, these companies are able to yield substantial returns in service delivery, risk reduction, cost reduction and cash flow management. At the same time, they create liquidity to fund acquisitions, product development, debt reduction, share buy-back programs and other strategic initiatives.
Keywords: economic uncertainty; shareholders; capital management best practices